Recall, for discrete-time finite length signals, the definition of the DFT and the inverse DFT, both in its normalized form:
$(DFT)~~X[k]= \sum_{n=0}^{N-1} x[n]\, \frac{e^{-j \frac{2\pi}{N}kn}}{\sqrt N} \\[2mm](Inverse DFT)~~x[n] = \sum_{k=0}^{N-1} X[k]\, \frac{e^{j \frac{2\pi}{N}kn}}{\sqrt N}$
and in its much more commonly used un-normalized form:$(DFT)~~X[k] = \sum_{n=0}^{N-1} x[n]\, e^{-j \frac{2\pi}{N}kn} \\[2mm]
(Inverse DFT)~~x[n]= \frac{1}{N}\sum_{k=0}^{N-1} X[k] \, e^{j \frac{2\pi}{N}kn}$A signal $x[n]$ and its DFT $X[k]$ (recall there is a one-to-one correspondence) are referred to as a DFT PAIR. The DFT has a variety of properties, which we will now consider.
The dft and its inverse are periodic
The DFT is defined for finite-length (length $N$) signals; so, for $x[n]$, $n$ runs from $0$ to $N-1$, as does $k$. But let is us see what happens when we consider a value of $k$ outside this range in the DFT formula, say $X[k+lN]$, where $l$ is some nonzero integer:
$\begin{align*}X[k+l N]&=~ \sum_{n=0}^{N-1} x[n]\,e^{-j \frac{2\pi}{N}(k+l N)n}\\&=\sum_{n=0}^{N-1} x[n]\, e^{-j \frac{2\pi}{N}kn} e^{-j \frac{2\pi}{N}l N n}\\&=\sum_{n=0}^{N-1} x[n]\, e^{-j \frac{2\pi}{N}kn}\cdot 1\\&=\sum_{n=0}^{N-1} x[n]\, e^{-j \frac{2\pi}{N}kn}\\&= X[k]
\end{align*}$As $X[k+lN]=X[k]$, the DFT is periodic:
By the same token, the inverse DFT is also periodic:
$\begin{align*}x[n+l N]&=~ \frac{1}{N}\sum_{k=0}^{N-1} X[k]\,e^{j \frac{2\pi}{N}k(n+lN)}\\&=\sum_{k=0}^{N-1} X[k]\, e^{j \frac{2\pi}{N}kn} e^{j \frac{2\pi}{N}klN}\\&=\sum_{k=0}^{N-1} X[k]\, e^{j \frac{2\pi}{N}kn}\cdot 1\\&=\sum_{k=0}^{N-1} X[k]\, e^{j \frac{2\pi}{N}kn}\\&= x[n]
\end{align*}$Again this is to be expected because the complex harmonic sinusoids of the inverse DFT sum are periodic. This also further illustrates the fact that any finite-length signals can be understood as a single period of a periodic signal.
Dft frequency ranges
A complex harmonic sinuoids $e^{j(\frac{2\pi}{N}k)n}$ has, by definition, a frequency of $\frac{2\pi}{N}k$, which may label as $\omega_k$. In the DFT of a signal of length $N$, the variable $k$ rangers from $0$ to $N-1$, which corresponds to frequencies from $0$ to (just about) $2\pi$:
However, as we saw above, since the DFT is periodic, $0$ to $N-1$ is not the only range of $k$ we may use to express the DFT. Since $X[k]=X[k-N]$, we may let $k$ run from $-\frac{N}{2}$ to $\frac{N}{2}-1$ (for even $N$, that is; for odd $N$ it would be $-\frac{N-1}{2}$ to $\frac{N-1}{2}$):
Shifts in time and frequency
Let $x[n]$ and $X[k]$ be a DFT pair (i.e., $X[k]$ is the DFT of $x[n]$). A circular shift in time on $x[n]$ will produce a phase shift on $X[k]$:
$x[(n-m)_N]~\stackrel{\textrm{DFT}}{\longleftrightarrow}~ e^{-j\frac{2\pi}{N}km} X[k]$To prove this relationship, we first note that for the circular shift $(n-m)_N$, there is some integer $l$ such that $(n-m)_N=n-m+lN$. We will use that fact for a change of variables in our proof:
$\begin{align*}\textrm{DFT}\{x[(n-m)_N]\}&=\sum_{n=0}^{N-1} x[(n-m)_N]\, e^{-j \frac{2\pi}{N}kn}\\&\textrm{Let }r=(n-m)_N=n-m+lN\\&=\sum_{r=0}^{N-1} x[r]\,e^{-j \frac{2\pi}{N}k (r+m-lN)}\\&=\sum_{r=0}^{N-1} x[r]\,e^{-j \frac{2\pi}{N}kr}e^{-j \frac{2\pi}{N}m}e^{-j \frac{2\pi}{N}lN}\\&=e^{-j \frac{2\pi}{N}m}\sum_{r=0}^{N-1} x[r]\,e^{-j \frac{2\pi}{N}kr}\cdot 1\\&=e^{-j\frac{2\pi}{N}km} X[k]\end{align*}$
As you might expect from the symmetrical similarities between the DFT and inverse DFT, a comparable relationship exists in the other direction as well. A circular shift in the frequency domain of a signal results in the modulation of the signal in the time domain:$e^{j\frac{2\pi}{N}l n} \, x[n] ~\stackrel{\textrm{DFT}}{\longleftrightarrow}~ X[(k-l)_N]$
The proof of this property follows the same approach as that of the first.
Bacteria doesn't produce energy they are dependent upon their substrate in case of lack of nutrients they are able to make spores which helps them to sustain in harsh environments
_Adnan
But not all bacteria make spores, l mean Eukaryotic cells have Mitochondria which acts as powerhouse for them, since bacteria don't have it, what is the substitution for it?
Assimilatory nitrate reduction is a process that occurs in some microorganisms, such as bacteria and archaea, in which nitrate (NO3-) is reduced to nitrite (NO2-), and then further reduced to ammonia (NH3).
Elkana
This process is called assimilatory nitrate reduction because the nitrogen that is produced is incorporated in the cells of microorganisms where it can be used in the synthesis of amino acids and other nitrogen products
There are nothing like emergency disease but there are some common medical emergency which can occur simultaneously like Bleeding,heart attack,Breathing difficulties,severe pain heart stock.Hope you will get my point .Have a nice day ❣️
_Adnan
define infection ,prevention and control
Innocent
I think infection prevention and control is the avoidance of all things we do that gives out break of infections and promotion of health practices that promote life
Lubega
Heyy Lubega hussein where are u from?
_Adnan
en français
Adama
Got questions? Join the online conversation and get instant answers!